ANALYSIS OF INCENTIVES AND THEIR EFFECTS ON EMPLOYEE WORK PRODUCTIVITY AT PT. "X" - Farradia, Yuary (International Journal of Multidisciplinary Research and Literature, 2022)
The organization or company has abundant resources, raw materials, capital, and technology. Still, if its human resources do not support it, its previously planned goals are difficult to achieve. The provision of incentives in the company is good and on time, so that employee work productivity is getting better. In addition to providing incentive wages, another factor that affects productivity is years of service. This quantitative research aims to measure/know the effect of providing incentives on employee productivity. This research method is useful for giving direction to researchers. It will guide researchers on how the research sequence will carry out and explain the stages related to the scope of research, population and samples, data and data sources, and data analysis methods.             Based on the results of the analysis above, it can conclude that incentives have a significant effect on the work productivity of employees in the production division of PT. X. Partially, incentives have a considerable impact on employee work productivity because they have an at- count value that is greater than the t-value table (2.816> 2.01). Meanwhile, simultaneously incentives also affect work productivity because it has a calculated F value greater than the F table value (7.932> 4.04).